2018
DOI: 10.1111/birt.12404
|View full text |Cite
|
Sign up to set email alerts
|

Opting for home birth in rural Bangladesh: An assessment of the current status and reasons

Abstract: Background: In Bangladesh, over half of women give birth at home, generally without the support of a skilled birth attendant. In this article, we examined the decisionmaking around birthplace and explored the reported reasons of preferring home birth over facility birth in a rural district of Bangladesh. Methods: A cross-sectional household survey with 1367 women was conducted in Brahmanbaria district. Choice of birthplace and actual place of birth were the main outcomes of interest. Associations between the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…In Sub-Saharan African countries, such as Tanzania, a high proportion of births are attended at home by non-qualified providers such as TBA, siblings, or neighbors, and it has been described that a lack of formal education, scarce telecommunication access, low acceptance to ANC services, low socioeconomic status, and geographic location were all related to the choice of home over institutional birth ( Moshi & Mbotwa, 2020 ). In Bangladesh (South Asia region), another country with a high proportion of home births, low family-perceived importance of institutional delivery, financial constraints, fear of cesarean section, and husbands not allowing delivery at health establishments were associated with having births at home ( Perkins et al, 2019 ). In general, LMICs present the highest proportions of home births and share the presence of factors that increase the probability of home birth care.…”
Section: Discussionmentioning
confidence: 99%
“…In Sub-Saharan African countries, such as Tanzania, a high proportion of births are attended at home by non-qualified providers such as TBA, siblings, or neighbors, and it has been described that a lack of formal education, scarce telecommunication access, low acceptance to ANC services, low socioeconomic status, and geographic location were all related to the choice of home over institutional birth ( Moshi & Mbotwa, 2020 ). In Bangladesh (South Asia region), another country with a high proportion of home births, low family-perceived importance of institutional delivery, financial constraints, fear of cesarean section, and husbands not allowing delivery at health establishments were associated with having births at home ( Perkins et al, 2019 ). In general, LMICs present the highest proportions of home births and share the presence of factors that increase the probability of home birth care.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, binary logistic regression models are most commonly used. Perkins et al [22] and Ahinkorah et al [23] attempted to uncover the determinants of the delivery of health facilities by using a binary logistic regression model but identified only individual factors. However, community factors also influence medical care.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the Bangladesh Maternal Health Strategy does not acknowledge pain management as a critical issue in rendering birth services. 17 Although some studies demonstrated that fear of cesarean serves as a barrier to seeking birth in a health facility, 18,33 in this context, for some women, undergoing cesarean could have been the only means to access some form of pain management.…”
Section: Discussionmentioning
confidence: 99%